Analisis Implementasi Manajemen Risiko pada UMKM Tasikmalaya (Studi Kasus UMKM Mie Baso Sarirasa 81) - Soni Santana; Irham Khairul Muttaqin; Lanina Astrid Chrysant Vrij; Angelina Asivadibrata; Nabilah Fitria Kamaludin; Azizah Ghina Aulia; Syti Sarah Maesaroh (Jurnal Bina Manajemen, 2023)
This study aims to analyze the various risks that may exist and the strategies that will be carried out by Mie Bakso Sari Rasa 81 This research uses a qualitative approach and data collection techniques in this study using interviews with UMKM Mie Baso Sarirasa 81 with online meet conference media. The results obtained are the risks that occur most often and become a high-level category in UMKM Mie Bakso Sarirasa 81 are marketing risks and financial risks, namely rising raw material prices and operational risks including the absence of SOPs in the use of production machines, human resources who lack understanding in products expired. To minimize the occurrence of MSME risks, it is necessary to identify and then carry out analysis and management of these risks. Management that can be done is by innovating products, making attractive promotions in online media, looking for other suppliers, making operational SOPs in writing, being selective in recruiting HR and providing marketing training to HR.